Quality of Life of Perimenopausal Women Seeking Health Care for Low Back Pain in Meghalaya - A Qualitative Study - Challam, Manroi; Rao, P. Arathi; Shylla, Badondor; Hossain, Shaikh Shah (Indian Journal of Nursing Sciences, 2024)
Background: Low back pain (LBP) is an important clinical, social, economic, and public health problem affecting the population. In India, the prevalence of LBP has been found to range from 6.2% to 92% with an increase of prevalence with age and female preponderance. The objective is to understand the quality of life of perimenopausal women seeking health care for LBP. Methods: A qualitative research was conducted in a rural setting of West Jaintia Hills District, Meghalaya from January to June 2018 and included perimenopausal women aged 40–50 years who had sought health care for LBP. The participants were selected using purposive sampling. Data were collected from 29 participants using an interview guide. Simultaneously, data collection and the analyzing of data were carried out. After interviewing the participants, the transcripts were prepared and translation was done. The data were read thoroughly to develop codes and categories. The participants were described in terms of sociodemographic details using descriptive statistics Results: Mean age of the participants is 45 years. 38% of the participants did not have any kind of formal education. The results showed that the majority of the participants were daily wage earners and preferred seeking health care from the government facilities. Financial problems and lack of education played an important role in prioritizing work over their health. Conclusion: The study showed that perimenopausal women considered work a priority over their health and financial problems play an important role in influencing the kind of work that they do. Educating and creating awareness among the community members are important to reduce the burden of LBP and on ways to prevent and manage it.